2019
DOI: 10.1016/j.ihj.2019.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of frontal QRS-T angle in predicting survival after primary percutaneous coronary revascularization/coronary artery bypass grafting for ST-elevation myocardial infarction

Abstract: Background Frontal QRS-T angle (FQRST) has previously been correlated with mortality in patients with stable coronary artery disease, but its role as survival predictor after ST-elevation myocardial infarction (STEMI) remains unknown. Methods We evaluated 267 consecutive patients with STEMI undergoing reperfusion or coronary artery bypass grafting. Data assessed included demographics, clinical presentation, electrocardiograms, medical therapy, and one-year mortality. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 24 publications
2
5
0
6
Order By: Relevance
“…The fQRSTa more than 90° was found to be an independent predictor of death, appropriate implantable cardioverter‐defibrillator shock, or resuscitated cardiac arrest in nonpaced patients with nonischemic cardiomyopathy 23 . Two hundred sixty‐seven patients with ST segment elevation myocardial infarction (STEMI) were evaluated by Sawant et al 24 and those who had wider fQRSTa had 2.04 times more mortality rates. A study by Dogan et al 25 including 340 patients with STEMI found fQRSTa to be related with coronary atherosclerotic burden.…”
Section: Discussionmentioning
confidence: 99%
“…The fQRSTa more than 90° was found to be an independent predictor of death, appropriate implantable cardioverter‐defibrillator shock, or resuscitated cardiac arrest in nonpaced patients with nonischemic cardiomyopathy 23 . Two hundred sixty‐seven patients with ST segment elevation myocardial infarction (STEMI) were evaluated by Sawant et al 24 and those who had wider fQRSTa had 2.04 times more mortality rates. A study by Dogan et al 25 including 340 patients with STEMI found fQRSTa to be related with coronary atherosclerotic burden.…”
Section: Discussionmentioning
confidence: 99%
“…По данным других авторов, больные с ОКС или ИМ с увеличением fQRS-T по сравнению с меньшим fQRS-T были старше [5][6][7][8], у них чаще встречались перенесенный ИМ [5,6,8], сердечная недостаточность [5,7,8], снижение ФВ ЛЖ [4,7]. Отмечалось более частое наличие многососудистого поражения [5] и поражение ствола левой коронарной артерии [7]. Кроме того, у больных с увеличением fQRS-T ИМбпST развивался чаще, чем ИМпST [7,8].…”
Section: Discussionunclassified
“…В ряде исследований продемонстрирована роль fQRS-T как диагностического критерия при подозрении на ИМ, независимого прогностического критерия кардиальной и общей смертности в раннем и отдаленном периодах у больных с острым ИМ с подъемом сегмента ST (ИМпST) и без подъема сегмента ST (ИМбпST), что значительно повысило интерес к fQRS-T и sQRS-T в настоящее время [4][5][6][7][8].…”
Section: оригинальные статьи §unclassified
See 1 more Smart Citation
“…9,10 Importantly, as a sign of instability in the myocardial conduction system, increased fQRST angle, particularly an angle >90°, is a predictor of arrhythmic substrates and is significantly associated with arrhythmic events and mortality in a wide variety of patients with cardiovascular diseases. 11,19,20 Besides the P wave indices, ventricular depolarization and repolarization abnormalities also seem to be associated with atrial electrophysiological abnormalities, occurrence of atrial arrhythmias and Af. [21][22][23] Moreover, a significant association between abnormal fQRST angle and emergence of Af has been reported.…”
Section: Ta B L E 1 Clinical and Electrocardiographic Characteristics Of Patient Groupsmentioning
confidence: 99%